Understanding the The Consumer Behavior of Smokers through Microeconomics Theory in Islamic Perspective - Khairunnisa Musari (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
Smoking in microeconomics included in the Theory of Consumer Behavior. This theory discusses how the consumers allocate income between different heads and how they decide how much to consume now and how much to save for future. In turn, it bears implications for macroeconomic policies. Further, many literatures explain that smoking has a negative impact in health, norms and ethics, and economic side. In Islamic economics, the law of smoking is not explicitly and expressly mentioned by the Qur'an and Sunnah. The jurists seek its solution through ijtihad. However, mostly studies which discussed about sharia issues corroborates that this activity is haraam and should be abandoned. No many studies focused on the Islamic macro-microeconomics side. Hence, in order to explain the cigarettes, smokers, and smoking activity in Islamic economics side in the future, this paper try to discuss about the smokers behavior in the microeconomics theory. Understanding the consumer behavior of smokers is difficult. But, referring to the theory of consumer behavior, smoking activity can be justified because the consumer is believed rational if they fulfill the all of axioms of preferences. The smokers behavior will try to be understood in three steps: consumer preferences, budget constraints, and consumer choices. JEL Classification: D01, D10, D11, D12, D14